Enhancement in Solar Cells Efficiency by Luminescent Down-Shifting layers - Ahmed, Hind; Mc Cormack, Sarah (My University, 2013)
In this paper, core-shell semiconductor quantum dots (QDs) CdSeS/ZnS with emission at 490 nm and 450 nm were investigated for their use in luminescent down-shifting (LDS) layers. Luminescent quantum yield (LQY) of the QDs measurements in solution proposed that they were suitable candidates for inclusion in LDS layers. QDs were encapsulated in poly(methyl,methacrylate) (PMMA) polymer matrix and films were fabricated of 134 ± 0.05 microns. Selections of organic dyes from BASF Lumogen F range were also investigated for their use as LDS layers; Violet 570 and Yellow 083. The addition of LDS layers containing Violet 570 dye demonstrated a unity LQY when encapsulated within a PMMA matrix. A PV device of an LDS layer of Lumogen Violet 570 deposited on top of a crystalline silicon cell was fabricated where it was demonstrated to increase the efficiency of the cell by 34.5% relative.
PUBLISHED
Keywords: Spectral losses; Solar cell efficiency; Down-shifting; Luminescent materials; Quantum dots; Nanoscience & Materials